2017
DOI: 10.4041/kjod.2017.47.3.176
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the gingival biotype and the width of keratinized gingiva in the mandibular anterior region of individuals with different dental malocclusion groups and levels of crowding

Abstract: ObjectiveTo evaluate the relationship of gingival thickness (GT) and the width of keratinized gingiva (WKG) with different malocclusion groups and the level of crowding.MethodsA total of 187 periodontally healthy subjects (121 females and 66 males) who presented at the Faculty of Dentistry in Yüzüncü Yıl University for orthodontic treatment were enrolled in the study. The individuals involved in the study were divided into three groups; Angle Class I malocclusion, Angle Class II malocclusion, and Angle Class I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 21 publications
5
27
0
6
Order By: Relevance
“…In conclusion, characterizing the morphologic and phenotypic features of GB in relation to other oral and facial structures is relevant when planning and performing dental procedures in the fields of prosthetics, occlusion, implants, and orthodontics (31)(32)(33)(34). Developing new economical and nontraumatic methods to accurately identifying GB and correlating GB with associated factors such as the occurrence of malocclusion (35)(36)(37) should be part of future research efforts about preventable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, characterizing the morphologic and phenotypic features of GB in relation to other oral and facial structures is relevant when planning and performing dental procedures in the fields of prosthetics, occlusion, implants, and orthodontics (31)(32)(33)(34). Developing new economical and nontraumatic methods to accurately identifying GB and correlating GB with associated factors such as the occurrence of malocclusion (35)(36)(37) should be part of future research efforts about preventable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] compared orthodontically treated adults with Angle Class III to subjects with Angle Class I and Class II malocclusions and found that patients having excessive dental compensations in the Angle Class III group had thrice as many teeth with labial gingival recession. Several other studies, however, did not find the association between the WKT or GT and the Angle classification [ 20 , 23 , 42 , 43 ]. As mentioned before, no previous study considered WITS.…”
Section: Discussionmentioning
confidence: 94%
“…[ 8 ] Our results are in accordance with the study done by Kaya et al . 2017[ 21 ] who reported that in Angle's Class III group, the gingival thickness of the mandibular right central and lateral incisor had thin phenotype. [ 16 ] As stated by Wennström 1996[ 19 ] when the buccolingual thickness of the gingiva decreases, then the apicocoronal height also decreases.…”
Section: Discussionmentioning
confidence: 99%